Direct Imaging of the Induced‐Fit Effect in Molecular Self‐Assembly. Issue 12 (12th February 2019) - Yang, Zechao; Lotze, Christian; Corso, Martina; Baum, Sebastian; Franke, Katharina J.; Pascual, José I.
Abstract: Molecular recognition is a crucial driving force for molecular self‐assembly. In many cases molecules arrange in the lowest energy configuration following a lock‐and‐key principle. When molecular flexibility comes into play, the induced‐fit effect may govern the self‐assembly. Here, the self‐assembly of dicyanovinyl‐hexathiophene (DCV6T) molecules, a prototype specie for highly efficient organic solar cells, on Au(111) by using low‐temperature scanning tunneling microscopy and atomic force microscopy is investigated. DCV6T molecules assemble on the surface forming either islands or chains. In the islands the molecules are straight—the lowest energy configuration in gas phase—and expose the dicyano moieties to form hydrogen bonds with neighbor molecules. In contrast, the structure of DCV6T molecules in the chain assemblies deviates significantly from their gas‐phase analogues. The seemingly energetically unfavorable bent geometry is enforced by hydrogen‐bonding intermolecular interactions. Density functional theory calculations of molecular dimers quantitatively demonstrate that the deformation of individual molecules optimizes the intermolecular bonding structure. The intermolecular bonding energy thus drives the chain structure formation, which is an expression of the induced‐fit effect. Abstract : Noncontact atomic force microscopy resolves that individual dicyanovinyl‐hexathiophenes molecules are deformed to energetically unfavorable configurations by linear intermolecular hydrogen bonds upon self‐assembly into chains on Au(111). Density functional theory calculations demonstrate that the deformation of individual molecules optimizes the intermolecular bonding structure, therefore, contributes additional binding energy to the whole system, which is a direct manifestation of the "induced‐fit effect."